Addition of Olive Leaf Extract (OLE) for Producing Fortified Fresh Pasteurized Milk with an Extended Shelf Life - Rosa Palmeri; Lucia Parafati; Daniela Trippa; Laura Siracusa; Elena Arena; Cristina Restuccia; Biagio Fallico (MDPI AG, 2019)
An olive leaf extract (OLE) has been tested in vitro for its antibacterial activity and ability to inhibit α-glucosidase enzyme. OLE was also evaluated for its potential, when added to pasteurized milk, to preserve nutritional parameters and to limit microbial growth, thus prolonging shelf life. In vitro assays demonstrated a strong antibacterial efficacy of OLE mainly against Bacillus cereus and the capacity to inhibit α-glucosidase enzyme (IC50) when used at 0.2 mg oleuropein/mL. The milk fortification with OLE at 3.6 mg of oleuropein/mL of milk reduced total mesophilic bacteria at undetectable level after 6 d (expiration date) and by 1 log CFU/mL after 10 d. Moreover, OLE addition at 1.44 and 3.6 mg of oleuropein/mL of milk significantly reduced fat and lactose losses up to 10 d. The results motivate the use of the OLE to make a new functional milk with an extended shelf life.